SiRNA Mediated Gene Silencing: A Mini Review - Baby Joseph; Ajisha S.U; Jeevitha M.V (Graduate Program of Syiah Kuala University, 2012)
Abstract - RNA interference (RNAi) technology has become a novel tool for silencing gene expression in cells or organisms. RNA interference is the process that double-stranded RNA induces the homology-dependent degradation of cognate mRNA mediated by 21-23 nucleotide short interfering RNA (siRNA). RNA interference is a powerful mechanism of gene silencing that underlies many aspects of eukaryotic biology. On the molecular level, RNAi is mediated by a family of ribonucleoprotein (RNP) complexes called RNA-Induced Silencing Complexes (RISCs), which can be programmed to target virtually any nucleic acid sequence for silencing. The ability of RISC to locate target RNAs been co-opted by evolution many times to generate a broad spectrum of gene silencing pathways. The study about the Silencing of gene expression by siRNA is rapidly becoming a powerful tool for genetic analysis and represents a potential strategy for therapeutic product development. In this study, the applications of siRNA expressing recombinant adenovirus system in plants, animals and in cancer gene therapy are given importance with its modifications